Pengembangan Website Pendaftaran Online Sekolah Menengah Pertama Botupingge Berbasis User-Friendly - suleman, sinta; Harun, Sulastri (Teknik Informatika Fakultas Ilmu Komputer Universitas Ichsan Gorontalo, 2025)
The current new student registration system still relies heavily on traditional methods, such as collecting physical files, often causing obstacles such as long queues, recording errors, and potential data loss. This study aims to develop an online registration website for Botupingge Middle School that is user-friendly and accessible to various groups. This application is designed to manage registration data in a computerized manner, eliminating the constraints of manual systems that are often slow and prone to errors. This application also provides long-term benefits in storing historical data of applicants that can be used for evaluation and strategic planning in the future. The development of this application is an innovative step to support more modern and professional education governance.